Validation of Experimental Cooling Performance of Multi-Stage Thin-Film Thermoelectric Devices via Numerical Simulation - Yu Ning; Longzhou Li; Ping Wei; Shaoqiu Ke; Wanting Zhu; Xiaolei Nie; Danqi He; Mingrui Liu; Wenyu Zhao (Micromachines)
In-plane thermoelectric thin-film cooling devices are considered a promising solution for thermal management in electronic systems. However, the actual cooling performance is far below that of regular bulk cooling devices, making the design of thin-film devices much more difficult. In this work, a numerical analysis of the cooling performance of single-leg thin-film devices and multi-stage cascaded thin-film devices was conducted to understand the depressed cooling performance. The effects of input current, operating environment, substrate, and contact resistance on cooling performance were investigated and compared with the experimental data. The results show that under ideal conditions, including vacuum environment, absence of substrate, and no contact resistance, the maximum cooling temperature difference simulated by the finite element method (105.4 K) closely matches the theoretical value estimated from the ZT-based calculation (96.6 K). Under practical conditions, such as within atmosphere and with substrate and contact resistance, the simulated maximum temperature difference (2.1 K) fits well with the experimental value (1.1 K). These findings demonstrate that substrate effects, contact resistance, and operating environment can significantly impair the cooling performance of in-plane film thermoelectric devices, although high-performance thermoelectric materials were used. This study provides a guidance for the design and parameter optimization of thermoelectric thin-film cooling modules.